Coping with cognitive impairment and dementia: Rural caregivers' perspectives. (July 2016) - Branger, Camille; Burton, Rachel; O'Connell, Megan E; Stewart, Norma; Morgan, Debra
Caregiving in a rural context is unique, but the experience of rural caregivers is understudied. This paper describes how rural caregivers cope with caring for a loved one diagnosed with mild cognitive impairment or dementia using qualitative description to generate a low-inference summary of a response to an open-ended question. This approach allowed these rural caregivers to describe their positive experiences in addition to the more commonly explored caregiver experiences related to stress. Analyses of coping revealed use of social support, engaging in relaxing and physical activity, and cognitive reframing. In addition, caregivers reported strong faith and religiosity, and to a lesser frequency behavioral changes, checking in with the person with dementia via telephone, and joint activity. Predominantly, these methods reflect approach-based strategies. The current data suggest that these caregivers manage well and adopt adaptive coping strategies to meet the demands of the caregiving role.